Peran Pemerintah Daerah dalam Pengelolaan Anggaran Pendidikan untuk Meningkatkan Akses dan Kualitas Pendidikan - Suryani, Yeni; Pertiwi, Ila Indah; Mustafa, Ivni Alfrisqa; Mulawarman, Widyatmike Gede; Haryaka, Usfandi (Lembaga Yasin AlSys, 2025)
Education is a constitutional right and a pillar of national development. The government allocates a minimum of 20% of the budget, with a total of IDR 665 trillion in 2024. However, increasing the budget does not guarantee equitable quality. The average length of national school is 8.92 years, but Papua and NTT are still below 7.5 years. The purpose of this study is to analyze the role of local governments in the management of education budgets, as well as to assess the extent to which this management contributes to improving access and quality of education in the regions. This research uses a descriptive qualitative approach with the aim of gaining an in-depth understanding of the role of local governments in managing education budgets and their impact on improving access and quality of education. Based on the results of the analysis, it is shown that the allocation and distribution of the education budget in Indonesia does not fully reflect the principle of justice between regions. Although most regions have met the minimum provisions for education spending in the APBD, the achievement of indicators such as average length of schooling, pure participation rate, and national assessment results still show striking gaps. For example, DKI Jakarta has the highest RLS of 11.31 years, while some provinces such as Papua are still below 7.5 years. Intermediate APM also varied, with Papua at 60.5% and East Nusa Tenggara at 63.2%. In terms of quality, DKI Jakarta and Yogyakarta show the percentage of student literacy and numeracy competency above 80%, while Papua is below 60%. This proves that the large proportion of the budget does not automatically guarantee equitable educational achievements. Therefore, the quality of governance and the effectiveness of program implementation are key factors in realizing equitable access and quality of education throughout Indonesia.